Analysis of Rob Flood Disaster Risk in the Coastal Area in Indah Nelayan Village - Harahap, Tria Astrid Nabila; Friska, Mutia; Susilawati, Susilawati; Tanjung, Adillah Maharani; Bara, Talita Shafiqah Batu; Sari, Wulan Dwi Citra (PROMOTOR, 2025)
Tidal floods are a natural phenomenon where sea water seeps onto land when sea levels rise, which can cause damage to property and even loss of life. Indah Fisherman's Village means one of the Medan Labuhan Districts, Medan City, North Sumatra. Nelayan Indah Village is an area that is prone to flooding caused by high tides. Method: This research uses a qualitative research methodology with a descriptive analytical approach. Researchers using this research method aim to provide an overview of the risk of flood disasters in the Belawan area. Objective: The aim of this research is to identify and analyze the level of risk faced by the people of the Belawan area, as well as formulate effective mitigation strategies to reduce the impact of this disaster on society and the environment. Results: The results of this research are that sea water is getting higher, water infiltration is no longer there, causing water to go towards land because there is no barrier because several mangrove plants are submerged, the fort is destroyed, because the waves drag the boat to land so it hits the fort and causes the fort to be destroyed or It can be called abrasion, damage to embankments due to eroding ship movements, broken embankments increase the risk of flooding. Conclusion: The results of this study highlight that tidal floods have the potential to harm people's livelihoods, damage household infrastructure, and disrupt economic activities and daily life but for fishermen it is profitable in their livelihoods because they get stranded fish.